Răspuns:
a. x=1, y=1 ; b. x=1, y=2
Explicație pas cu pas:
a.
[tex]2x - 2y + 3x + 6y = 9 \\ 5x + 4y = 9 \\ x = \frac{9 - 4y}{5} \\ 12x - 4y - 2x - 2y = 4 \\ 10x - 6y = 4 \\ 10 \times \frac{9 - 4y}{5} - 6y = 4 \\ 18 - 8y - 6y = 4 \\ 14y = 14 \\ y = 1 \\ x = \frac{9 - 4 \times 1}{5} = \frac{9 - 4}{5} = \frac{5}{5} \\ x = 1[/tex]
b.
[tex]15x - 10y - 7x + 14y = 16 \\ 8x + 4y = 16 \\ y = \frac{16 - 8x}{4} \\ y = 4 - 2x \\ 3x + 12y + 4x - 10y = 11 \\ 7x + 2y = 11 \\ 7x + 2 \times (4 - 2x) = 11 \\ 7x + 8 - 4x = 11 \\ 3x = 3 \\ x = 1 \\ y = 4 - 2 \times 1 = 4 - 2 \\ y = 2[/tex]